(untitled) (International Journal of Natural Sciences, 2016)
The study was conducted to evaluate the effects of triclabendazole and nitroxynil against fascioliasis in goat for a period of 28 days on 20 black bengal goats. Among hundred goats, twenty were selected for this study which was suffering from liver fluke (Fasciola gigantica) infection and were marked by tagging. Twenty goats were randomly divided into four groups (A, B, C and D) where each group comprising of five goats. Group A were treated with tablet fasinex (triclabendazole, Novartis Ltd, Bangladesh) orally at the dose rate of 12 mgkg-1body weight, group B were treated with acinex (triclabendazole, ACI Ltd, Bangladesh) orally at the dose rate of 12 mgkg-1body weight and group C were treated with nitronex injection (nitroxynil, Renata Ltd, Bangladesh) subcutaneously at the dose rate of 10 mgkg-1 body weight. Goats of group D was kept as infected control group without giving any treatment. A significant (P<0.01) reduction of egg per gram (EPG) count was found on 7th, 14th, 21st and 28th days of treated goats of group A, B and C, respectively. The EPG count of control group were significantly (P<0.01) increased 7 day onwards up to experimental period. Reduction of mean EPG on 7th, 14th, 21st and 28th day after treatment in group A, B and C were 81.48%, 81.25% and 83.04%, respectively, whereas in control group the mean EPG were 22.43%. Of the hematological parameters, TEC, Hb and PCV values were lower on day 0 but turned to increase (p<0.01) on day 28 of the study. On the other hand, ESR and TLC were higher before treatment (day 0) but decreased significantly (p<0.01) on day 28.The body weight increased significantly (P<0.01) after treatments in group A, B and C respectively except untreated control. This result may indicate that three commercial anthelmintics contain triclabendazole and nitroxynil against fascioliasis in goat and nitroxynil have higher efficacies on egg per gram (EPG), hematological parameters and body weight against fascioliasis in goat. Additional detailed studies are required to prevent and control of fascioliasis in goats by using a routine prophylactic anthelmintics measurement. International Journal of Natural Sciences (2015), 5(2) 46-51